Dampak Pengendalian Hama Terpadu terhadap Pendaftaran dan Penggunaan Pestisida di Indonesia - Kasumbogo Untung (Universitas Gadjah Mada, 2004)
Integrated Pest Management (IPM) legally has been adopted as the principle of crop protection practices in Indonesia since 1992 through the release of Law No.12 /1992 on Crop Husbandry System and Government Regulation No.6/1995 on Crop Protection. Data was collected from the national registration authority and the national statistic agency for evaluating the impact of IPM policy to the registration and use of pesticides by farmers. The data showed that the number of registered pesticide formulations, and the production and distribution of pesticides have increased since 1989. The number of formulations reached the peak in 2002 with a total of 813. On the other hand, the production was most in 1996 (80,000 ton) and the highest use of pesticide by rice farmer occurred in 1991 (4,72 kg pesticide/ha). Most of present registered pesticide formulations are generic. The data indicated that nationally IPM has not been significantly altered the registration, distribution and uses of pesticides by farmers in Indonesia. Comprehensive and integrated efforts must be established and implemented seriously by all stakeholders to institutionalize and implement IPM.